COMPARATIVE ANALYSIS OF ALTAI AND KYRGYZ MUSICAL INSTRUMENTS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the parallels and similarities in the musical instruments of the Altai and Kyrgyz people, which shed light on the common sources and roots of the origin of the musical culture of both peoples.
Keywords: culture, music, roots, origins, komuz, topshuur, ooz komuz, choor.